Effect of experimental periodontitis on cardiac functions: a comprehensive study using echocardiography, hemodynamic analysis, and histopathological evaluation in a rat model - Elhaieg, Asmaa; Farag, Ahmed; Elfadadny, Ahmed; Yokoi, Aimi; Hendawy, Hanan; Mandour, Ahmed S.; Tanaka, Ryou (Frontiers in Veterinary Science, 2023)
Periodontitis is a prevalent and severe dental condition characterized by the gradual degradation of the bone surrounding the teeth. Over the past two decades, numerous epidemiological investigations have suggested a potential link between periodontitis and cardiovascular disease. However, the complex mechanistic relationship between oral health issues and cardiovascular disorders remains unclear. This study aimed to explore comprehensively the cardiac function through various methods, including conventional echocardiography, intraventricular pressure gradient (IVPG) analysis, Speckle Tracking Echocardiography (STE), and hemodynamics analysis. Ligature-induced periodontitis was established in a group of rats while the second group served as sham. The successful establishment of the periodontitis model was confirmed through staining and radiographic examination of the affected mandibles. X-ray films and methylene blue staining revealed alveolar bone resorption in the affected first molar in the model rats, confirming the successful induction of periodontitis. The rats with periodontitis displayed a decrease in ejection fraction compared to the sham group, accompanied by a decrease in Mid-to-apical IVPG and Mid IVPG. Lower values of strain rate were recorded in the apical segment of the septum, the middle segment of the septum, and the basal segment of the lateral free wall in the periodontitis group, which was associated with histopathological examination showing some degree of myocardial tissue damage. Conversely, rats with periodontitis showed an increase in heart rate, end-systolic volume, and arterial elastance when compared to the sham rats. However, they also exhibited a decrease in stroke work, stroke volume, cardiac output, and end-systolic pressure. This study highlights that experimental periodontitis leads to cardiac dysfunction especially compromised systolic function and myocardial relaxation, indicating an increased risk of cardiovascular events in clinical periodontitis cases. The comprehensive assessment of cardiac function, hemodynamics, and histopathological evaluation underscores the profound impact of periodontitis on heart functions within this specific experimental model.